Who is Involved: A Critical Discourse Analysis of Al Jazeera and CNN Headlines on Yahya Sinwar's Death (Van Leeuwen's Theory) - Zahra Intan Paradita; Maulaya Arinil Haq; Muhammad Fikri Assyamil; Muhammad Zainal Muttaqien (Universitas Sebelas Maret, 2025)
The media significantly shapes public opinion and influences societal perceptions of diverse local and worldwide issues. Consequently, news coverage has the potential to shape public discourse significantly. This study employs a descriptive qualitative approach to analyze patterns in the reporting of Yahya Sinwar's death by CNN and Al Jazeera, utilizing Theo Van Leeuwen's (2008) framework for critical discourse analysis.Through the application of Van Leeuwen's theory, the study examines how Western and Middle Eastern media providers frame Sinwar's death and represent the social actors involved in his assassination. Van Leeuwen's framework categorizes the representation of social actors into two primary strategies: exclusion, encompassing suppression and backgrounding, and inclusion, which includes Activation/Passivation, Genericization/Specification, Assimilation, Association, Indetermination, Functionalization/Identification, and Personalization/Impersonalization. The analysis highlights distinct differences in the framing strategies of the two media providers. CNN and Jazeera differ in their framing strategies, with CNN emphasizing individual actions and a direct narrative style, while Jazeera uses a context-driven approach, emphasizing collective experiences and connecting individual events to larger systemic issues